(untitled) (AYUSHDHARA, 2025)
Fibroadenoma is painless, unilateral, benign bone tumour that’s a solid, not fluid- filled, lump. It occurs most generally in women between 14 and 35 but can be set up at any age. Granthi can be equated with all types of small in size glandular or nodular swelling developing mostly due to benign tumours and cysts. There is no direct reference for Stana Granthi in Ayurveda. But, Stana granthi or the fibroadenoma is treated as the Mamsaja Granthi or the Kaphaja Granthi based on the Lakshanas. As per Ayurvedic science, Granthi or Arbuda is defined as the growths caused by the abnormal vitiation of Dosha and Dushya which may develop in any part of the body, which are multiple in numbers present in different locations with various presentations. Acharya Charaka has explained these types in the chapter of "Shotha. Chedana karma one among the Astavidha shastra karmas and the first Shastra karma explained by Acharya Sushrutha has shown significant results in the management of Stanagranthi. Chedana involves excision of part of the body/ tissue using various instruments. Chedana is indicated in Granthi and Vrana that is along with veins (Siras), which have Sthula edges, which are hard and in Adhimansaja vikara. Hence the present study attempted in evaluating the role of Chedana karma in the management of Stanagranthi.